Vienna Church of St. Charles & Polytechnic School - Corbould, George James (engraver):::Creator::::::::::::; Batty, Robert, 1789-1848 (artist):::Contributor:::::::::::: (London; Rodwell & Martin New Bond Street; United Kingdom)
Engraving of the Church of St. Charles & Polytechnic School in Vienna